Particle breakage and energy dissipation of carbonate sands under quasi-static and dynamic compression - Xiao, Yang (2021)
Quasi-static and dynamic compression tests are conducted on carbonate sand using a Material Testing System and a modified split Hopkinson pressure bar, respectively. The particle size distributions (PSDs) of carbonate sand before and after loading are measured via laser diffractometry. The stress–strain curves demonstrate that the carbonate sand investigated in this study exhibits strain rate effects. The stress–strain curves show slightly different features for quasi-static and dynamic loading conditions. The particle breakage extent, which is quantified from the PSDs of the samples before and after loading, is investigated at different stress levels and input energy values. The breakage efficiency under the quasi-static loading condition is higher than that under the dynamic loading condition. As a result, the particle breakage extent is higher under the quasi-static loading condition than under the dynamic loading condition at the same stress level. Furthermore, the particle breakage modes are highly dependent on stress. The breakage modes under the dynamic loading condition change from attrition and abrasion at low stress levels, resulting in the appearance of plateaus in the grading curves, to fracture at high stress levels, resulting in the disappearance of plateaus in the grading curves.